Question 1
Given the sequence
31, 61, 91, 121,...
An arithmetic sequence has a constant difference 'd' and is defined by
computing the differences of all the adjacent terms
61 - 31 = 30, 91 - 61 = 30, 121 - 91 = 30
The difference between all the adjacent terms is the same and equal to
d = 30
As the first term of the sequence is:
a₁ = 31
now substituting a₁ = 31 and d = 30 in the nth term of the sequence


Now, putting n = 36 to determine the 36th term




Thus, the 36th term is:

Question 2
Given the sequence
-34, -44, -54, -64, ...
An arithmetic sequence has a constant difference 'd' and is defined by
computing the differences of all the adjacent terms

The difference between all the adjacent terms is the same and equal to

As the first term of the sequence is:
a₁ = -34
now substituting a₁ = -34 and d = -10 in the nth term of the sequence


Now, putting n = 26 to determine the 36th term




Thus, the 26th term is:
